RESPONS PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) TERHADAP PEMBERIAN ABU JANJANG KELAPA SAWIT DAN PUPUK UREA PADA MEDIA PEMBIBITAN - Sarah Vitrya Sidabutar; Balonggu Siagian; Meiriani Meiriani (Universitas Sumatera Utara, 2013)
The Response of Cocoa Seedlings Growth (Theobroma cacao L.) for Giving Palm Bunch Ash andUrea Fertilizer in The Media of Nursery. The research was conducted in the field UPT BBI,Tanjung Selamat at an altitude ± 57 meters above sea level since May 2012 until August 2012 usingRandomized Block Design (RBD) factorial with two factors. The first factor is palm bunch( 0, 10, 20, and 30 g/polybag). The second factor is urea fertilizer (0, 3, 6, and 9 g/polybag).The Parameter observed includes plant hight (cm), number leafs (sheet), and fresh weight ofcrown (g.) The result of reseach showed that giving palm bunch ash influential not significantly toall parameters. Urea fertilizer influential significantly on plant height and number of leafs.Interaction between giving palm bunch ash and urea fertilizer influential not significantly to allparameters.Key Words : Palm bunch ash, urea fertilizer, cocoa, nursery